EVALUASI KUALITAS LAYANAN PERPUSTAKAAN MI PERSIS 29 BANDUNG MENGGUNAKAN MODEL LIBQUAL+ - Ramadhan Nadhif Firdaus; Angga Hadiapurwa; Yayu Wulandari (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2025)
This research assessed the quality of library services at MI Persis 29 Bandung from the perspective of its teaching staff. Recognizing the vital role of elementary school libraries in fostering literacy and supporting the educational process, this study employed the LibQUAL+ model to understand teachers' perceptions. The methodology involved a survey administered to teachers, which gauged their minimum, desired, and perceived levels of service across three core dimensions: Affect of Service, Information Control, and Library as Place. The investigation revealed that while the library services generally met or slightly surpassed teachers' minimum expectations in several aspects, a consistent gap existed when compared to their desired levels of service across all dimensions. Positive adequacy in areas such as basic staff friendliness and ease of locating books was noted. However, significant shortcomings were identified in achieving ideal service levels, particularly concerning the desire for more proactive and knowledgeable staff, a richer collection of diverse reading materials including up-to-date information, and a more comfortable, quiet, and inspiring library environment. Based on these findings, the study offered targeted recommendations aimed at enhancing the overall quality and responsiveness of the library services to better meet the needs of its users.